DEVELOPMENT OF CRITICAL THINKING SKILLS: COMPARATIVE ANALYSIS OF MEDIA LITERACY LEVEL IN BOSNIA AND HERZEGOVINA AND LATVIA - Murinska-Gaile, Sandra; Hadžialić, Sabahudin (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The aim of this paper is to look on level of media literacy and activities in this field in two countries – Latvia and Bosnia and Herzegovina. People are exposed to a flow of diverse content of information and opinions, there it is important to discuss about media education and it`s outcome – the media literacy. Media literacy helps people to analyze, evaluate, and create messages thus develops people's critical and creative abilities. The survey about credibility of mass media, critical use of information, understanding of media literacy in each country, institutions promoting media literacy and the impact of media literacy on political decision making was carried out. The main hypothesis of this case study was that media literacy is basic presumption of the establishing the critical thinking of society of developed democratic consciousness.The comparative analysis showed that sociological aspect in the area of Bosnia and Herzegovina within the deep division in the society itself, with the lack of consensual awareness creates presumption trust completely into the mass media, while in the case of Latvia there is just few answers related to the existing media literacy.